Трагическое начало в художественном мире повести Бориса Львовича Васильева „Завтра была война” - Przybysz, Anna Katarzyna (Studia Rossica Posnaniensia, 2015)
The aim of this article is to analyze the influence of war on the process of shaping personality in the young generation based on the novel Tommorow Was War which was written by Boris Vasilyev, i.e. one of the writers who survived the Second World War. The main emphasis is on the development of the heroic element in an ordinary human being, opposition to injustice, the struggle for human dignity and the issue of a moral choice.